POSSIBILITIES OF FIBRE-REINFORCED CEMENT COMPOSITES USING TO RESTORE THE WATER SUPPLY PIPELINE - Viktor V. Shishkin; Savva V. Skorikov (Наука. Инновации. Технологии, 2022)
General approach to the design of the composition of the fibrous mixtures, of a kind used for the application of maintenance of the coating on the inner surface of the pipe, is given in the article. Recommendations are given on the opportunities to use a certain type of fiber when restoring.